PENERAPAN TERAPI AKTIFITAS KELOMPOK (TAK) TERHADAP PERUBAHAN KONSEP DIRI REMAJA DENGAN HARGA DIRI RENDAH - Siti Fatimah; Yessy Dessy Arna; Yetti Wilda (JURNAL PENELITIAN KESEHATAN, 2014)
Based on data Komnas PA ( 2012) the prevalence of low self esteem in adolescents in Indonesia compared with adolescents in the region , teenagers in Indonesia is likely to experience low self esteem by 2%. This study used a quasi experiment with research design approach pre and post-test design. Researchers conducted a partial sample of existing interventions with intervention A (brainstorming) and partial sample of group B (therapy group activity), then the observations pre and post-test, the Wilcoxon statistical test and Mann-Whitney. This study aimed to examine the effect of the application of Therapeutic Activity Group (TAG) to changes in self-concept adolescents with low self esteem at SMU Sidoarjo. Population is students of SMU 4 Sidoarjo with a sample of 98 people. After the pre-test 42 known students of experiencing a negative self-esteem then divided into 2 groups: control group and treatment groups, each group consisting of 21 students of the negative self-esteem. The results showed 98 students of SMU 4 Sidoarjo, nearly half the 42 students of experiencing a negative self-esteem. In the control group, 21 individuals with known negative self-esteem, after brainstorming done 17 of them became positive self-esteem and in the treatment group of 21 people with negative self-esteem, after TAK 20 of them became positive self-esteem. The statistical result obtained by the Wilcoxon p = 0.000, it can be concluded NOT giving more influence on adolescent self-concept changes compared to brainstorm on students of SMU 4 Sidoarjo. Community nurses should be able to make a schedule TAG with the guidance counselor at the school on UKS program to improve self-esteem adolescents toward positive so that they feel that every teenager has the potential to move forward.  Keywords: Adolescent Growth, Self-concept, self-esteem.